A method for efficiently preparing precipitated barium sulfate
Patent Information
- Application Number
- CN202610093985.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-23
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2046-01-23
AI Technical Summary
然而,该工艺存在硬脂酸耐温性不足导致产品颜色不稳定、以及工序复杂等问题
与现有技术相比,本发明的有益效果是:
Smart Images

Figure IMAGE_57A3986F-359E-433B-ADA4-02A1C6D0211F 
Figure IMAGE_702B6809-6DBC-4F54-97D4-9A84625E0A98
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical technology, and in particular to a method for the efficient preparation of precipitated barium sulfate. Background Technology
[0002] Precipitated barium sulfate, with its excellent chemical inertness, optical shielding properties, and radiation absorption capabilities, is widely used in coatings, plastics, rubber, and electronics. As downstream applications become more sophisticated, the requirements for particle size, dispersibility, and compatibility are increasing. However, existing technologies still have shortcomings in terms of quality, energy consumption, environmental protection, and stability, making it difficult to simultaneously meet the comprehensive demands of high quality and low cost.
[0003] Existing technologies mainly include the following four categories: One method is the carbothermic reduction process for barite. For example, Chinese patent CN118811851A discloses a method for purifying barite, which prepares high-purity barium sulfate through flotation, acid washing, and carbon calcination. However, this process requires high temperatures, resulting in huge energy consumption; moreover, impurities in the raw materials easily form acid-soluble barium salts, leading to low barium conversion rate and large waste emissions. The accompanying acid washing and defluorination process also increases environmental protection and equipment costs.
[0004] Second, there are acid roasting and solid waste resource recovery processes. For example, Chinese patent CN115676868A utilizes hydrochloric acid dissolution, calcination conversion, and reprecipitation to recover barium sulfate from salt mud. Although this type of process achieves resource utilization, it generates a large amount of acid-containing waste liquid and hydrogen sulfide gas, resulting in significant environmental pressure and requiring highly corrosion-resistant equipment. Furthermore, the process is lengthy, and fluctuations in raw materials can easily lead to instability in product purity, whiteness, and particle size, and the recovery rate of acid-soluble barium salts is generally low.
[0005] Thirdly, there is the liquid-phase precipitation process. As exemplified by Chinese patent CN106186028A and existing research, a barium chloride and sodium sulfate system is used, with the addition of EDTA, sodium stearate, and other additives to control particle size. Although micron-sized particles can be obtained under laboratory conditions, this process is highly sensitive to parameters such as reaction concentration, pH, and temperature. During industrial scale-up, uneven micro-mixing can easily lead to a wider particle size distribution and poor batch-to-batch reproducibility, making it difficult to meet the demands of high-end applications.
[0006] Fourthly, surface modification processes. Regarding the hydrophilic and oleophobic properties of barium sulfate, Chinese patent CN104387805A discloses a surface treatment process for modified ultrafine natural barium sulfate specifically for powder coatings, using stearic acid in combination with a coupling agent for composite treatment. However, this process suffers from problems such as insufficient temperature resistance of stearic acid leading to unstable product color and complex procedures. While Chinese patent CN201611153450.X uses stearate pretreatment to improve dispersibility, it also points out that composite materials are still prone to surface pitting and decreased gloss at high filler ratios. Furthermore, existing modifiers have significant differences in compatibility with different matrices such as PA66 and PVC, limiting their versatility.
[0007] In summary, existing technologies either suffer from high energy consumption and low conversion rates, heavy pollution and long processes, parameter sensitivity and poor stability, or insufficient compatibility. Therefore, there is an urgent need to develop a new technology for the preparation of precipitated barium sulfate that combines low energy consumption, high quality, excellent compatibility, and large-scale stable production capabilities. Summary of the Invention
[0008] The purpose of this invention is to address the problems in the existing technology where precipitated barium sulfate prepared by traditional processes is prone to agglomeration, uneven particle size distribution, high impurity content, low product purity and barium element yield, and poor dispersion stability. Therefore, this invention proposes a highly efficient method for preparing precipitated barium sulfate.
[0009] To achieve the above objectives, the present invention adopts the following technical solution: A method for efficiently preparing precipitated barium sulfate includes the following steps: Step 1: The raw barite ore is crushed to a particle size ≤5mm using a crusher, and then further pulverized to 100-200 mesh using an air jet mill. After impurity removal through a combination of gravity separation and flotation, it is transferred to a rotary kiln under a nitrogen atmosphere for calcination and activation. The specific operation of the combined impurity removal is as follows: ① Gravity separation: using a density of 1.8-2.0 g / cm³. 3 The process involves: 1) Heavy media suspension: Utilizing the density difference between barite and silica / alumina gangue minerals, the powder is added to a separation device and allowed to stand for 20-30 minutes to separate the bottom barite concentrate from the upper gangue suspension, removing coarse gangue particles; 2) Flotation treatment: The gravity-separated concentrate is prepared into a slurry with a mass concentration of 25-35%, and 0.05-0.1% of a fatty acid collector and 0.1-0.2% of a sodium silicate depressant are added to adjust the slurry pH to 8-9. The ore is placed in a flotation machine for 15-20 minutes to selectively attach the beristone particles to the air bubbles and float to the surface, while the fine-grained silica and aluminum gangue remain in the slurry, achieving deep impurity removal. The beristone concentrate after flotation is dehydrated by vacuum filtration, dried at 100-105℃ for 1-2 hours, and then transferred to a rotary kiln. During the calcination process, the heating rate is controlled at 5-10℃ / min, and after heating to 1050-1150℃, it is calcined at a constant temperature for 2-4 hours. After cooling to room temperature, the calcined beristone powder is obtained. The aforementioned combined impurity removal process specifically addresses the difficulty in removing silicon and aluminum gangue from raw barium sulfate ore: gravity separation, as a pretreatment step, efficiently separates coarse gangue particles ≥50μm in diameter, reducing the load on subsequent flotation and avoiding separation difficulties caused by excessive mudding of gangue and barium sulfate during fine grinding; the flotation process, through selective adsorption of the collector on the surface of barium sulfate, combined with the shielding effect of inhibitors on silicon and aluminum gangue, achieves deep removal of fine-sized gangue, increasing the purity of barium sulfate concentrate to over 95%. After this process, the total content of silicon and aluminum impurities is reduced to below 0.5%, providing high-purity raw materials for subsequent calcination and sulfuric acid reaction. Combined with the adsorption and inhibition effect of modifiers on ionic impurities, the final result ensures that the content of silicon and aluminum impurities in the precipitated barium sulfate product is ≤0.03%, meeting the stringent requirements for low-ash fillers in high-end applications.
[0010] Step 2: Add calcined barite powder to the reactor, add anhydrous ethanol at a solid-liquid ratio of 1:(6-10) g / mL, start stirring at 300-500 r / min to disperse the powder evenly, then raise the temperature to 40-55℃, add the modifier, which is diluted with anhydrous ethanol to a 5-10% solution by mass, and add it over a period of 30-60 min. After the addition is complete, maintain the temperature and continue stirring for 1.5-3 h to obtain the barite activated system. Step 3: Add a 12-18% sulfuric acid solution to the barite activation system at a rate of 1-2 mL / min, keep the temperature at 45-65℃, and increase the stirring speed to 600-800 r / min. During the reaction, monitor the pH value of the system in real time with a pH meter. When the pH drops to 2.0-3.0, stop adding sulfuric acid and continue stirring for 30-60 min to obtain a suspension. Step 4: Transfer the suspension to a vacuum filtration device and use vacuum filtration at a vacuum degree of 0.07-0.09 MPa to separate the precipitate from the mother liquor. Wash the precipitate repeatedly with deionized water, using 3-5 times the mass of the precipitate each time, until the pH of the washing solution reaches 6.5-7.5 and no white precipitate is formed when tested with a barium chloride solution with a molar concentration of 0.1-0.2 mol / L. Then, transfer the washed precipitate to a forced-air drying oven and vacuum dry it at 105-120℃ for 5-8 hours. Subsequently, it is ultra-finely pulverized to D50≤1μm to obtain precipitated barium sulfate.
[0011] Preferably, in the second step, the mass of the modifier is 0.8-2.5% of the mass of the calcined barite powder.
[0012] Preferably, in the third step, the molar ratio of barium oxide to sulfuric acid in the activated barite powder is 1:1.02-1.05.
[0013] Through the above technical solution, the main component of barite is barium carbonate, which undergoes a thermal decomposition reaction after high-temperature calcination to produce barium oxide and carbon dioxide. This process simultaneously removes volatile impurities attached to the barite, including moisture, organic impurities, and some insoluble impurities. Calcium carbonate, magnesium carbonate, etc., are also converted into oxides. The surface of the calcined barium oxide is rich in hydroxyl groups and is extremely prone to absorbing water and agglomerating. When it reacts directly with sulfuric acid, it easily forms local supersaturated regions, resulting in severe agglomeration of the generated barium sulfate particles, which easily encapsulate impurities in the system.
[0014] The modifier precisely regulates the surface properties of barite through the synergistic effect of chemical and physical processes to solve the above problems: First, the siloxane groups in the modifier molecule hydrolyze to generate Si-OH, which undergoes a condensation reaction with the hydroxyl groups on the surface of barium oxide to form stable Si-O-Ba covalent bonds, making the modifier firmly anchored to the powder surface and preventing it from falling off during the reaction; Second, the polyethylene glycol long ether segments in the modifier molecule extend outward to create a steric hindrance effect, hindering the approach of adjacent barite particles, inhibiting particle agglomeration from the root, and ensuring that a uniform reaction interface can be formed on the surface of each particle; At the same time, the N atom on the pyridine ring at the end of the modifier has a lone pair of electrons and is weakly basic, which can inhibit the adsorption probability of impurity ions such as calcium, iron, magnesium, strontium, manganese, and lead ions in sulfuric acid solution through electrostatic repulsion, reducing the co-precipitation of impurities with barium sulfate.
[0015] After activation by a modifier, the barite powder undergoes a metathesis reaction with sulfuric acid solution under mild reaction conditions: barium oxide first reacts with hydrogen ions in sulfuric acid to form barium hydroxide, which then further combines with sulfate ions, or reacts directly with sulfuric acid, ultimately forming barium sulfate precipitate. During this process, the steric hindrance effect of the long polyethylene glycol ether chain allows sulfuric acid molecules to diffuse uniformly to the surface of each barite particle, preventing rapid crystal growth and aggregation caused by excessively high local sulfuric acid concentrations. The modifier's adsorption and inhibition of impurity ions further reduces the encapsulation of impurities in the barium sulfate precipitate, ensuring product purity. Excess sulfuric acid is controlled during the reaction to ensure the purity of the barium oxide. 2+ Complete conversion significantly improves product yield. Subsequent washing to remove soluble impurities, drying to remove moisture, and ultrafine grinding to optimize particle size ultimately yields high-purity, well-dispersible barium sulfate precipitate. The reaction route is as follows: Preferably, in the second step, the method for preparing the modifier includes the following steps: A1: γ-glycidyl etheroxypropyltrimethoxysilane and diamino-terminated polyethylene glycol were added to a three-necked flask equipped with a reflux reflux device, along with anhydrous ethanol and triethylamine. The mixture was heated to 70-90°C under nitrogen protection and stirred for 3-6 hours. After the reaction was completed, the solvent and unreacted substances were removed by vacuum distillation at 40-50°C and a vacuum degree of 0.08-0.09 MPa. The product A was then obtained by extraction, washing, concentration, and drying. A2: Add product A to a dry reactor, add anhydrous dichloromethane, then add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and stir at room temperature for 30-45 min for activation; according to the molar ratio of active hydroxyl group in product A to nicotinic acid 1:1.0-1.5, slowly add a nicotinic acid solution dissolved in anhydrous dichloromethane, with a nicotinic acid concentration of 0.1-0.2 g / mL. After the addition is complete, continue stirring at room temperature for 16-18 h. After the reaction is complete, filter out the insoluble matter, and then purify, concentrate and dry to obtain the modifier.
[0016] Preferably, in step A1, the molecular weight of the bi-amino-terminated polyethylene glycol is 2000-8000 Da, and the degree of polymerization is 45-180.
[0017] Preferably, in step A1, the mass ratio of γ-glycidyl etheroxypropyltrimethoxysilane to diamino-terminated polyethylene glycol is 1:3.5-6.0.
[0018] Preferably, in step A1, the amount of triethylamine used is 5-10% of the mass of the diamino-terminated polyethylene glycol.
[0019] Preferably, in step A2, the molar ratio of hydroxyl group to dicyclohexylcarbodiimide and 4-dimethylaminopyridine in product A is 1:1.2-1.5:0.05-0.1.
[0020] By controlling the excess amount of γ-glycidoxypropyltrimethoxysilane, the epoxy group in the γ-glycidoxypropyltrimethoxysilane structure undergoes a nucleophilic ring-opening addition reaction with the amino group at the end of the bi-amino polyethylene glycol structure under the action of triethylamine, generating product A containing a secondary hydroxyl group. The hydroxyl group in product A then undergoes a condensation esterification reaction with the carboxyl group in the nicotinic acid molecule in a dehydration condensation system of dicyclohexylcarbodiimide and 4-dimethylaminopyridine, ultimately preparing a modifier containing a pyridine ring, a long polyethylene glycol ether segment, and a siloxane group. The reaction route is as follows: Compared with the prior art, the beneficial effects of the present invention are: 1. The precipitated barium sulfate prepared by this invention has a purity of over 99.0%, a concentrate barium yield of over 95%, and a total barium yield of over 90%, which is far superior to most traditional processes and control schemes. The content of inorganic impurities such as calcium, magnesium, iron, strontium, manganese, and lead in the product can be controlled within 0.001%, and the content of silicon and aluminum impurities can be ≤0.03%. After ultrafine grinding, the particle size can be stably controlled with D50≤1μm. At the same time, after ultrasonic dispersion in an anhydrous ethanol system and standing for 24 hours, there is no stratification phenomenon, and the dispersion stability is good. It can meet the stringent requirements of filler purity, fineness, and dispersion compatibility in high-end fields such as coatings and electronics.
[0021] 2. The special modifier prepared by this invention combines siloxane groups, polyethylene glycol long ether segments, and pyridine ring structures. It can be firmly anchored to the surface of calcined barite powder through covalent bonds, and can also inhibit powder agglomeration through steric hindrance. At the same time, it can reduce the probability of impurity ion adsorption, thereby reducing the impurity encapsulation of barium sulfate precipitate from the source. Furthermore, the precise control of key parameters such as calcination heating rate, sulfuric acid drop acceleration rate, and system pH in the process can ensure uniform reaction, avoid abnormal crystal growth caused by local supersaturation, and improve the controllability and repeatability of the entire preparation process.
[0022] 3. This invention uses barite ore as a direct raw material, which can be converted into highly reactive barium oxide powder through calcination and activation. Compared with the traditional carbothermal reduction process, no additional reducing agent is required, reducing energy consumption and waste emissions. It also avoids the environmental protection problem of acidic wastewater generated by acid roasting process. At the same time, the operating parameters of each process are reasonable, and the equipment used is all conventional equipment in the chemical industry. The preparation process of the modifier can be connected with the main process. The overall process has no special harsh conditions, and the core reaction unit can be connected with the industrial production process. After targeted adaptation and adjustment (such as optimizing solvent substitution or simplifying purification operation), it can meet the requirements of industrial production. Detailed Implementation
[0023] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0024] Example 1: I. Preparation of precipitated barium sulfate: Step 1: The raw barite ore is crushed to a particle size of 5mm using a crusher, and then further pulverized to 100-mesh powder using an air jet mill. Impurities are removed through a combination of gravity separation and flotation: ① Gravity separation: using a density of 1.8g / cm³. 3① Heavy medium suspension: The powder was added to a separator and allowed to stand for 20 minutes to separate the bottom barite concentrate; ② Flotation treatment: The concentrate was prepared into a 25% (w / w) slurry, and 0.05% (w / w) of fatty acid collector and 0.1% (w / w) of sodium silicate inhibitor were added to the slurry. The pH was adjusted to 8, and the slurry was floated for 15 minutes. The scum (barite concentrate) was collected, dehydrated by vacuum filtration, dried at 100℃ for 1 hour, and then transferred to a rotary kiln under nitrogen atmosphere for calcination and activation. The heating rate was controlled at 5℃ / min during the calcination process. After heating to 1050℃, the temperature was kept constant for 2 hours. After cooling to room temperature, the calcined barite powder was obtained. Step 2: Add calcined barite powder to the reactor, add anhydrous ethanol at a solid-liquid ratio of 1:6 g / mL, start stirring at 300 r / min to evenly disperse the powder, then raise the temperature to 40℃, add 0.8% (by weight) of modifier from the calcined barite powder; dilute the modifier with anhydrous ethanol to a 5% (by weight) solution, add it over 30 min, and maintain the temperature and continue stirring for 1.5 h to obtain the barite activation system; Step 3: Add a 12% sulfuric acid solution to the barite activation system at a rate of 1 mL / min, keep the temperature at 45°C, and increase the stirring speed to 600 r / min. During the reaction, monitor the pH value of the system in real time with a pH meter. When the pH drops to 2.0, stop adding sulfuric acid and continue stirring for 30 min to obtain a suspension. Step 4: Transfer the suspension to a vacuum filtration device and use vacuum filtration at a vacuum degree of 0.07 MPa to separate the precipitate from the mother liquor. Wash the precipitate repeatedly with deionized water, using three times the mass of the precipitate each time, until the pH of the washing solution reaches 6.5 and no white precipitate is formed when tested with a 0.1 mol / L barium chloride solution. Then, transfer the washed precipitate to a forced-air drying oven and vacuum dry at 105℃ for 5 hours. Subsequently, it is ultra-finely pulverized to a D50 of 1 μm to obtain precipitated barium sulfate.
[0025] II. Preparation of Modifier: A1: 10g of γ-glycidyl etheroxypropyltrimethoxysilane and 35g of biamino-terminated polyethylene glycol (molecular weight 2000 Da, degree of polymerization 45) were added to a three-necked flask equipped with a reflux device. 90mL of anhydrous ethanol and 1.75g of triethylamine were added. The mixture was heated to 70℃ under nitrogen protection and stirred for 3h. After the reaction was completed, the solvent and unreacted substances were removed by vacuum distillation at 40℃ and a vacuum degree of 0.08MPa. The product A was then obtained by extraction, washing, concentration and drying. A2: Add 40g of product A to a dry reactor, add 124mL of anhydrous dichloromethane, then add 2.47g of dicyclohexylcarbodiimide and 0.61g of 4-dimethylaminopyridine, and stir at room temperature for 30min to activate. Add a solution of nicotinic acid dissolved in anhydrous dichloromethane at a molar ratio of 1:1.0 to the active hydroxyl group in product A, with a nicotinic acid concentration of 0.1g / mL. After the addition is complete, continue stirring at room temperature for 16h. After the reaction is complete, filter out the insoluble matter, and then purify, concentrate and dry to obtain the modifier.
[0026] Example 2: I. Preparation of precipitated barium sulfate: Step 1: The raw barite ore is crushed to a particle size of 5mm using a crusher, and then further pulverized to 180-mesh powder using an air jet mill. Impurities are removed through a combination of gravity separation and flotation: ① Gravity separation: using a density of 1.9g / cm³. 3 ① The heavy medium suspension was allowed to stand for 25 minutes to separate the barite concentrate; ② Flotation treatment: a 30% mass concentration slurry was prepared, and 0.08% of fatty acid collector and 0.15% sodium silicate inhibitor were added to the slurry. The pH was adjusted to 8.5, and flotation was carried out for 18 minutes. The concentrate was dehydrated by vacuum filtration, dried at 102℃ for 1.5 hours, and then transferred to a rotary kiln under nitrogen atmosphere for calcination and activation. The heating rate was controlled at 8℃ / min during the calcination process. After heating to 1100℃, the temperature was kept constant for 3 hours. After cooling to room temperature, the calcined barite powder was obtained. Step 2: Add calcined barite powder to the reactor, add anhydrous ethanol at a solid-liquid ratio of 1:8 g / mL, start stirring at 400 r / min to evenly disperse the powder, then raise the temperature to 45℃, add 2.0% (by weight) of modifier of calcined barite powder, the modifier is diluted with anhydrous ethanol to a mass fraction of 8%, the addition time is controlled at 45 min, after the addition is completed, maintain the temperature and continue stirring for 2 h to obtain the barite activation system; Step 3: Add a 16% sulfuric acid solution to the barite activation system at a rate of 1.5 mL / min, keep the temperature at 60°C, and increase the stirring speed to 700 r / min. Monitor the pH value of the system in real time using a pH meter during the reaction. Stop adding sulfuric acid when the pH drops to 2.5, and continue stirring for 45 min to obtain a suspension. Step 4: Transfer the suspension to a vacuum filtration device and use vacuum filtration at a vacuum degree of 0.08 MPa to separate the precipitate from the mother liquor. Wash the precipitate repeatedly with deionized water, using 4 times the mass of the precipitate each time, until the pH of the washing solution reaches 7.0 and no white precipitate is formed when tested with a 0.15 mol / L barium chloride solution. Then, transfer the washed precipitate to a forced-air drying oven and vacuum dry at 110℃ for 6 hours. Subsequently, it is ultra-finely pulverized to a D50 of 1 μm to obtain precipitated barium sulfate.
[0027] II. Preparation of Modifier: A1: 10g of γ-glycidyl etheroxypropyltrimethoxysilane and 47.5g of biamino-terminated polyethylene glycol (molecular weight 5000 Da, degree of polymerization 113) were added to a three-necked flask equipped with a reflux device. 173mL of anhydrous ethanol and 3.56g of triethylamine were added. The mixture was heated to 80℃ under nitrogen protection and stirred for 5h. After the reaction was completed, the solvent and unreacted substances were removed by vacuum distillation at 45℃ and a vacuum degree of 0.085MPa. The product A was then obtained by extraction, washing, concentration and drying. A2: Add 52g of product A to a dry reactor, add 186mL of anhydrous dichloromethane, then add 2.64g of dicyclohexylcarbodiimide and 0.67g of 4-dimethylaminopyridine, and stir at room temperature for 40min to activate. Add a solution of nicotinic acid dissolved in anhydrous dichloromethane at a molar ratio of 1:1.2 to the active hydroxyl group in product A, with a nicotinic acid concentration of 0.15g / mL. After the addition is complete, continue stirring at room temperature for 17h. After the reaction is complete, filter out the insoluble matter, and then purify, concentrate and dry to obtain the modifier.
[0028] Example 3: I. Preparation of precipitated barium sulfate: Step 1: The raw barite ore is crushed to a particle size of 5mm using a crusher, and then further pulverized to 200-mesh powder using an air jet mill. Impurities are removed through a combination of gravity separation and flotation: ① Gravity separation: using a density of 2.0g / cm³. 3 ① The heavy medium suspension was allowed to stand for 30 minutes to separate the barite concentrate; ② Flotation treatment: a 35% mass concentration slurry was prepared, and 0.1% fatty acid collector and 0.2% sodium silicate inhibitor were added to the slurry. The pH was adjusted to 9, and flotation was carried out for 20 minutes. The concentrate was dehydrated by vacuum filtration, dried at 105℃ for 2 hours, and then transferred to a rotary kiln under nitrogen atmosphere for calcination and activation. The heating rate was controlled at 10℃ / min during the calcination process. After heating to 1150℃, the temperature was kept constant for 4 hours. After cooling to room temperature, calcined barite powder was obtained. Step 2: Add calcined barite powder to the reactor, add anhydrous ethanol at a solid-liquid ratio of 1:10 g / mL, start stirring at 500 r / min to evenly disperse the powder, then raise the temperature to 55℃, add 2.5% (by mass) of modifier of calcined barite powder, the modifier is diluted with anhydrous ethanol to a 10% (by mass) solution, the addition time is controlled at 60 min, after the addition is completed, maintain the temperature and continue stirring for 3 h to obtain the barite activation system; Step 3: Add 18% sulfuric acid solution to the barite activation system at a rate of 2 mL / min, keep the temperature at 65°C, increase the stirring speed to 800 r / min, monitor the pH value of the system in real time with a pH meter during the reaction, stop adding sulfuric acid when the pH drops to 3.0, continue stirring for 60 min to obtain a suspension; Step 4: Transfer the suspension to a vacuum filtration device and use vacuum filtration at a vacuum degree of 0.09 MPa to separate the precipitate from the mother liquor. Wash the precipitate repeatedly with deionized water, using 5 times the mass of the precipitate each time, until the pH of the washing solution reaches 7.5 and no white precipitate is formed when tested with a 0.2 mol / L barium chloride solution. Then, transfer the washed precipitate to a forced-air drying oven and vacuum dry at 120℃ for 8 hours. Subsequently, it is ultra-finely pulverized to a D50 of 1 μm to obtain precipitated barium sulfate.
[0029] II. Preparation of Modifier: A1: 10g of γ-glycidyl etheroxypropyltrimethoxysilane and 60g of biamino-terminated polyethylene glycol (molecular weight 8000 Da, degree of polymerization 180) were added to a three-necked flask equipped with a reflux device. 350mL of anhydrous ethanol and 6g of triethylamine were added. The mixture was heated to 90℃ under nitrogen protection and stirred for 6h. After the reaction was completed, the solvent and unreacted substances were removed by vacuum distillation at 50℃ and a vacuum degree of 0.09MPa. The product A was then obtained by extraction, washing, concentration and drying. A2: Add 65g of product A to a dry reactor, add 338mL of anhydrous dichloromethane, then add 2.31g of dicyclohexylcarbodiimide and 0.92g of 4-dimethylaminopyridine, and stir at room temperature for 45min to activate. Add a solution of nicotinic acid dissolved in anhydrous dichloromethane at a molar ratio of 1:1.5 (nicotinic acid concentration 0.2g / mL) dropwise. After the addition is complete, continue stirring at room temperature for 18h. After the reaction is complete, filter out the insoluble matter, and then purify, concentrate and dry to obtain the modifier.
[0030] Comparative Example 1: Based on Example 2, the difference is that in the second step, product A is used as a modifier, and the rest is the same as in Example 2.
[0031] Comparative Example 2: Based on Example 2, the difference is that in the second step, the mass of the modifier is 0.7% of the mass of the calcined barite powder, and the rest is the same as in Example 2.
[0032] Comparative Example 3: Based on Example 2, the difference is that in step A1, a bi-amino-terminated polyethylene glycol with a molecular weight of 1000 Da was used as a raw material to prepare the modifier, and the rest is the same as in Example 2.
[0033] Comparative Example 4: Based on Example 2, the difference is that in step A1, a bi-amino-terminated polyethylene glycol with a molecular weight of 10000 Da was used as a raw material to prepare the modifier, and the rest is the same as in Example 2.
[0034] Comparative Example 5: Based on Example 2, the difference is that in the second step, the silane coupling agent γ-aminopropyltriethoxysilane is used instead of the modifier, and the rest is the same as in Example 2.
[0035] Comparative Example 6: Based on Example 2, the difference is that in the second step, polyethylene glycol hexadecyl ether is used instead of the modifier, and the rest is the same as in Example 2.
[0036] Comparative Example 7: Based on Example 2, the difference is that in the second step, the modifier is removed, and the rest is the same as in Example 2.
[0037] Test example: The performance of precipitated barium sulfate prepared in Examples 1-3 and Comparative Examples 1-7 was tested. The test results are shown in Table 1: The BaSO4 content and purity of the product were tested according to the method in standard GB / T2899-2017 "Industrial Precipitated Barium Sulfate". The mass fraction of barium sulfate, W1, was calculated as W1 = (m1 / m) × 100%, where m1 is the mass of the precipitate in grams (g), and m is the mass of the sample in grams (g). Inductively coupled plasma optical emission spectrometry (ICP-OES) was used to detect: ① the total mass of Ba element in the raw barium sulfate ore (m0); ② the mass of Ba element in the barium sulfate concentrate after flotation and impurity removal. (m1); ③ Mass of Ba element in the precipitated barium sulfate product (m2); Calculate two yield indicators: barium concentrate yield = (m2 / m1)×100%; total barium yield of raw ore = (m2 / m0)×100%; ICP-OES was used to detect the content of inorganic impurity elements (calcium, magnesium, iron, strontium, manganese, lead, silicon, aluminum) in the product; 1g of product was dissolved in 100mL of anhydrous ethanol, ultrasonically dispersed at 300W for 30min, and then allowed to stand for 24h. The system was visually observed to determine whether it was layered or settled, and the dispersion stability was judged.
[0038] Table 1. Performance test results of precipitated barium sulfate in the examples and comparative examples. Data Analysis: The precipitated barium sulfate prepared in Examples 1-3 exhibited excellent comprehensive performance: its silicon and aluminum impurity content was significantly lower than that of the comparative example, confirming the synergistic effect of the combined impurity removal process and the modifier, which can comprehensively control ionic impurities and insoluble gangue impurities, ensuring that the product meets the low ash content requirements of high-end fields; its inorganic impurity content (calcium, magnesium, iron, strontium, manganese, lead) was at an extremely low level and the silicon and aluminum impurity content was ≤0.03%; at the same time, the product had high purity and high concentrate barium yield and total barium yield of raw ore, and it could still maintain excellent dispersion stability without stratification after ultrasonic treatment and standing for 24 hours in an anhydrous ethanol dispersion system. These performance advantages are attributed to the combined effect of the steric hindrance effect of the modifier and the impurity adsorption inhibition effect.
[0039] Compared with Example 2, Comparative Example 1 showed an increase in the content of inorganic impurities (calcium, magnesium, iron, strontium, manganese, lead), a decrease in product purity and two yield indicators, and a slight stratification of dispersion stability. This is because Product A does not contain a pyridine ring, which cannot suppress the adsorption of impurity ions. At the same time, the lack of a complete modifier structure has a steric hindrance effect, which increases impurity encapsulation and affects particle dispersibility and reaction sufficiency.
[0040] Compared with Example 2, the inorganic impurity content (calcium, magnesium, iron, strontium, manganese, lead) of Comparative Example 2 increased, the product purity and yield decreased, and the dispersion stability showed slight stratification. This is because the amount of modifier was lower than the preferred range, which could not completely cover the surface of the barite powder, could not give full play to the steric hindrance effect to inhibit particle agglomeration, and could not effectively inhibit the adsorption of impurity ions.
[0041] Compared with Example 2, the inorganic impurity content (calcium, magnesium, iron, strontium, manganese, lead) of Comparative Example 3 was higher than that of Example 2, the purity and yield of the product decreased, and the dispersion stability became layered. This is because the molecular weight of the bi-amino-terminated polyethylene glycol is too low, the steric hindrance of the formed polyethylene glycol long ether chain is insufficient, which cannot effectively prevent particle aggregation, and at the same time affects the adsorption and inhibition effect on impurity ions, and the dispersion system has insufficient stability.
[0042] Compared to Example 2, Comparative Example 4 had higher levels of inorganic impurities (calcium, magnesium, iron, strontium, manganese, and lead), resulting in lower product purity and yield, and exhibited stratified dispersion stability. This is because the excessively high molecular weight of the diamino-terminated polyethylene glycol (PEG) leads to enhanced interactions between the long PEG ether chains, making them prone to entanglement and preventing uniform extension to form an effective spatial barrier. This entanglement not only disrupts the uniform diffusion of sulfuric acid molecules but also weakens the adsorption and inhibition of impurity ions, thereby reducing the dispersion stability of the system.
[0043] Compared with Example 2, the inorganic impurity content (calcium, magnesium, iron, strontium, manganese, lead) of Comparative Example 5 increased significantly, the product purity and yield decreased significantly, and the dispersion stability was slightly stratified. This is because γ-aminopropyltriethoxysilane does not have the steric hindrance effect of polyethylene glycol long ether chain and the impurity adsorption inhibition effect of pyridine ring, which can neither avoid particle agglomeration nor reduce impurity encapsulation, and at the same time affect the sufficiency of the reaction.
[0044] Compared with Example 2, Comparative Example 6 had a higher content of inorganic impurities (calcium, magnesium, iron, strontium, manganese, lead), further reduced product purity and yield, and slight stratification in dispersion stability. This is because polyethylene glycol hexadecyl ether lacks siloxane groups and pyridine rings, which means it cannot firmly anchor to the surface of barite powder, cannot inhibit the adsorption of impurity ions, and has insufficient steric hindrance effect.
[0045] Compared with Example 2, Comparative Example 7 had the highest content of inorganic impurities (calcium, magnesium, iron, strontium, manganese, lead), the lowest product purity and yield, and the dispersion stability was stratified. This is because the lack of a modifier caused steric hindrance and impurity adsorption inhibition, making it easy for the barite particles to agglomerate and form local supersaturated regions during the reaction. In addition, a large number of impurity ions were encapsulated in the precipitate, and the product had extremely poor dispersibility.
[0046] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A method for efficiently preparing precipitated barium sulfate, characterized in that, Includes the following steps: Step 1: After crushing and pulverizing the raw barite ore, it is then subjected to a combination of gravity separation and flotation to remove impurities such as silica and aluminum gangue minerals. The ore is then transferred to a calcination device for calcination and activation. During the calcination process, the heating rate is controlled at 5-10℃ / min. After heating to 1050-1150℃, the temperature is kept constant for 2-4 hours. After cooling to room temperature, calcined barite powder is obtained. Step 2: Add calcined barite powder to the reactor, add dispersing solvent at a solid-liquid ratio of 1:6-10 g / mL, start stirring to uniformly disperse the powder, then raise the temperature to 40-55℃, add the modifier, maintain the temperature and continue stirring for 1.5-3 hours to obtain the barite activated system; wherein, the amount of the modifier is 0.8-2.5% of the mass of the calcined barite powder; the modifier is prepared by the following steps: A1: γ-glycidyl etheroxypropyltrimethoxysilane and diamino-terminated polyethylene glycol were added to a three-necked flask equipped with a reflux reflux device, along with anhydrous ethanol and triethylamine. Under nitrogen protection, the mixture was heated to 70-90°C and stirred for 3-6 hours. After the reaction was completed, the solvent and unreacted substances were removed by vacuum distillation at 40-50°C and a vacuum degree of 0.08-0.09 MPa. The product was then extracted, washed, concentrated, and dried to obtain product A containing active hydroxyl groups. The diamino-terminated polyethylene glycol had a molecular weight of 2000-8000 Da and a degree of polymerization of 45-180. A2: Add product A to a dry reactor, add anhydrous dichloromethane, then add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and stir at room temperature for 30-45 min for activation; according to the molar ratio of active hydroxyl group in product A to nicotinic acid 1:1.0-1.5, slowly add a nicotinic acid solution dissolved in anhydrous dichloromethane, with a nicotinic acid concentration of 0.1-0.2 g / mL. After the addition is complete, continue stirring at room temperature for 16-18 h. After the reaction is complete, filter out the insoluble matter, and then purify, concentrate and dry to obtain the modifier; Step 3: Add sulfuric acid solution with a mass fraction of 12-18% to the barite activation system at a rate of 1-2 mL / min, keep the temperature at 45-65℃ and maintain a suitable stirring speed. During the reaction, monitor the pH value of the system in real time with a pH meter. When the pH drops to 2.0-3.0, stop adding sulfuric acid and continue stirring for 30-60 min to obtain a suspension. Step 4: After solid-liquid separation, the precipitate is washed with deionized water until the pH of the washing solution reaches 6.5-7.5 and there is no sulfate residue. After drying, it is ultra-finely pulverized to D50≤1μm to obtain precipitated barium sulfate.
2. The application of a modifier in the activation of barite, characterized in that, The modifier is prepared by the following steps: A1: γ-glycidyl etheroxypropyltrimethoxysilane and diamino-terminated polyethylene glycol were added to a three-necked flask equipped with a reflux reflux device, along with anhydrous ethanol and triethylamine. Under nitrogen protection, the mixture was heated to 70-90°C and stirred for 3-6 hours. After the reaction was completed, the solvent and unreacted substances were removed by vacuum distillation at 40-50°C and a vacuum degree of 0.08-0.09 MPa. The product was then extracted, washed, concentrated, and dried to obtain product A containing active hydroxyl groups. The diamino-terminated polyethylene glycol had a molecular weight of 2000-8000 Da and a degree of polymerization of 45-180. A2: Add product A to a dry reactor, add anhydrous dichloromethane, then add dicyclohexylcarbodiimide and 4-dimethylaminopyridine, and stir at room temperature for 30-45 min for activation; according to the molar ratio of active hydroxyl group in product A to nicotinic acid 1:1.0-1.5, slowly add a nicotinic acid solution dissolved in anhydrous dichloromethane, with a nicotinic acid concentration of 0.1-0.2 g / mL. After the addition is complete, continue stirring at room temperature for 16-18 h. After the reaction is complete, filter out the insoluble matter, and then purify, concentrate and dry to obtain the modifier.
3. The application according to claim 2, characterized in that, In step A1, the mass ratio of γ-glycidyl etheroxypropyltrimethoxysilane to diamino-terminated polyethylene glycol is 1:3.5-6.
0.
4. The application according to claim 2, characterized in that, In step A1, the amount of triethylamine used is 5-10% of the mass of the diamino-terminated polyethylene glycol.
5. The application according to claim 2, characterized in that, In step A2, the molar ratio of the active hydroxyl group to dicyclohexylcarbodiimide and 4-dimethylaminopyridine in product A is 1:1.2-1.5:0.05-0.1.
Citation Information
Patent Citations
Special surface treatment process for modified superfine natural barium sulfate for powder coating
CN104387805A
Production method and application of precipitated barium sulfate
CN106186028A
Pretreatment method of precipitated barium sulfate
CN106752103A
Method for recovering barium sulfate from solid waste barium-containing salty mud
CN115676868A
Barite purification method
CN118811851A